Advanced Porosity Modeling and Lithology Analysis Based on Sonic Log and Core Data for Arkose Sandstone Reservoir: Habban Field - A Al-Hasani, IM Saaed, AM Salim, HT Janjuhah, . (2017)
Porosity represents the rock's capacity to trap fluid. It is the main quality indicator for hydrocarbon-bearing reservoirs. The reservoir porosity is a crucial input to estimate hydrocarbon reserves by volumetric method, which is known as oil originally in place (OOIP). It also plays a key role in the hydraulic unit identification, rock typing, net reservoir, and net pay analyses to determine the best potential oil-bearing layers for perforation and oil production.